2020
DOI: 10.3390/ma13204672
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium-Based Ionic Liquid as Efficient Corrosion Inhibitor for AA 6061 Alloy in HCl Solution

Abstract: The corrosion inhibition performance of an imidazolium-based ionic liquid (IL), 1-butyl-3-methylimidazolium thiocyanate (BMIm), was studied on AA 6061 alloy in 1 M HCl solution at 303 K, 333 K, and 363 K by gravimetric tests, potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS) analysis. Scanning electron microscopy with energy dispersive X-ray (SEM-EDX) and X-ray photoelectron spectroscopy (XPS) were used to detect the surface morphologies and chemical composition of the surface film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…[14,15]. Ionic liquids are popularly used as sustainable and green corrosion inhibitors for metal [5,7,12,[15][16][17][18]. Many researchers used electrochemical tests and surface investigations to obtain the inhibition efficiency and found that the adsorption process of an inhibitor can be described by Langmuir adsorption [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15]. Ionic liquids are popularly used as sustainable and green corrosion inhibitors for metal [5,7,12,[15][16][17][18]. Many researchers used electrochemical tests and surface investigations to obtain the inhibition efficiency and found that the adsorption process of an inhibitor can be described by Langmuir adsorption [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the most effective inhibitors have π-systems or multiple bonds, and organic compounds containing O, P, N, or S atoms have a good corrosion performance [20]. But it is very difficult to choose the favorite ILs as effective corrosion inhibitors for a specific application since there are about 10 18 kinds of ionic liquids that can be formed with the present available cations and anions. Fortunately, with the development of computer technology and related theory, in recent years, Savaş et al further applied the quantum chemical study and molecular dynamics (MD) to explore corrosion inhibition mechanisms and corrosion inhibition performance [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the other reported inhibitors [61,62] showed slightly higher % IE than ABT but at a very low concentration of HCl medium (0.01 and 0.1 M HCl). However, ABT exhibited a lower % IE than two other reported inhibitors [63,64].…”
Section: A Comparison Of Inhibition Performance Of Abt With Reported ...mentioning
confidence: 55%
“…The N 1s spectrum of the sample evaluated in the presence of PILs (Figure ) reveals the presence of the >CNH + – species at 401.6–402.0 eV. These peaks are attributed to the presence of the imidazolium ring of PILs. ,, The N–H and/or N–Fe bond(s) detected at 399.9 eV , is associated with the presence of the amide group of the monomers in the three PILs and/or N–Fe coordination bond(s), respectively. The characteristic C 1s signals of the sample are observed in Figure .…”
Section: Results and Discussionmentioning
confidence: 97%
“…These peaks are attributed to the presence of the imidazolium ring of PILs. 73 , 75 , 79 The N–H and/or N–Fe bond(s) detected at 399.9 eV 74 , 80 84 is associated with the presence of the amide group of the monomers in the three PILs and/or N–Fe coordination bond(s), respectively. The characteristic C 1s signals of the sample are observed in Figure 12 .…”
Section: Results and Discussionmentioning
confidence: 99%